Rom og etikk Fortellinger om ambivalens - S. Rønsdal, Kaia (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
Space and Ethics. Ambiguous Narratives interprets encounters with people in various contexts from a spatial perspective. What are the ethical implications when people often labelled "strangers" are situated in the same spaces as other persons? Traditionally, ethical space theory seeks to elucidate the experience of being an outsider in a marginalized space. This book, however, does the opposite. The authors problematize the ethical and spatial impact when all act in the same space. This is the central topic of the book, which is intended for both professionals and everyday practitioners.